INTEGRASI SOSIAL MASYARAKAT MULTIETNIS DALAM PERSPEKTIF FUNGSIONAL STRUKTURAL DI DESA DURIAN KECAMATAN SUNGAI AMBAWANG - Ricksen Sonora Roffies; Yohanes Bahari; Fatmawati Fatmawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2019)
This study aims to determine the social integration of multiethnic communities in a functional structural perspective in Durian Village, Sungai Ambawang District. The research method used is descriptive in the form of qualitative research. The source of this research data is obtained by observation, interview and documentation. The results showed that the process of social integration of multiethnic communities occurred because of the existence of individual sociolinguistic abilities, ethnorelativism attitudes, mechanisms for problem solving, especially persuasively and the application of customary sanctions and the strength of local leadership. Meanwhile, the results of social integration are the creation of social stability because of the acculturation of local wisdom values and the development of a high sense of tolerance resulting in inter-ethnic cooperation and interdependence.